Enhancement of Methane Detection in Tunable Diode Laser Absorption Spectroscopy Using Savitzky–Golay Filtering - Shichao Chen; Xing Tian; Tong Mu; Jun Yuan; Xile Cao; Gang Cheng (Photonics)
In order to enhance gas absorption efficiency and improve the detection sensitivity of methane, a gas absorption cell with an effective optical path length of 29.37 m was developed, employing tunable diode laser absorption spectroscopy (TDLAS) and a distributed feedback (DFB) laser with a center wavelength of 1.654 μm as the light source. However, despite these advancements, the detection accuracy was still limited by potential signal interference and noise. To address these challenges, the Savitzky–Golay (S-G) filtering technique was implemented to optimize the TDLAS detection signal. Experimental results indicated a significant enhancement in detection performance. For a methane concentration of 92 ppm, the application of the S-G filter improved the signal-to-noise ratio by a factor of 1.84, resulting in a final device detection accuracy of 0.53 ppm. This improvement demonstrates the effectiveness of the S-G filter in enhancing detection sensitivity, supporting high-precision methane monitoring for atmospheric analysis and various industrial applications.